Speech and language therapy for aphasia: parameters and outcomes. Issue 5 (3rd May 2020) - Thomas, Lucie; Lander, Louise; Cox, Nicholas; Romani, Cristina
ABSTRACT: Background : Speech and language therapy is effective in improving language outcomes in acquired aphasia. However, it remains unclear which therapy parameters are most important to ensure gains. Published literature reviews are limited by the heterogeneity of the protocols considered, conflation of important parameters, and/or the paucity of the studies reviewed. Aims : We carried out two new reviews of the effects of therapy parameters on language outcomes, addressing some of the limitations of previous reviews and focusing on the effect of the number of words treated, cumulative dosage of therapy, and frequency of sessions. Method and Procedure : In the first review (N studies = 48; N participants = 387), we considered only studies involving picture naming, in order to focus on a relatively homogeneous protocol. Here, we correlated therapy parameters with language outcomes. In the second review, we included a broader range of protocols, in order to select studies where either dosage (N studies = 8; N participants = 211) or frequency of therapy (N studies = 9; N participant = 114) were contrasted, while other aspects of therapy were controlled for. Given the paucity of these studies, here we only presented descriptive analyses of studies that did, or did not, show significant effects of dosage or frequency on language outcomes. Results : The therapy parameters used by the reviewed studies show the use of limited resources (studies were characterised by small doses, short duration and few words treated). Percentage increase in number of words correct compared to baseline did not correlate or correlated negatively with all therapy parameters. Number of words gained, instead, correlated positively and significantly with the number of words treated and the number of words treated per hour. Controlled studies provided some evidence for the benefits of higher dosages of therapy, but no evidence in favour of either massed or distributed practice. Conclusions : Results provided limited evidence that people with aphasia benefit from a higher dosage of therapy and no evidence at all that a massed mode of delivery is to be preferred. Instead, our results provide strong evidence of the benefits of treating larger sets of words, and more words per hour within the range of therapy durations and dosages reviewed by our study. They also suggest caution in using percentage increase as a measure of outcomes, as this will favour studies treating fewer words. Above all, our results highlight the lack of well-powered studies to assess the effects of therapy parameters on outcomes in controlled conditions.